Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s10826-009-9295-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Family Expressiveness as Reported by Mothers and Fathers Related to Children’s Social Anxiety Symptoms?

Abstract: We examined family expressiveness as reported by mothers and fathers with respect to children's report of social anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…We identified four more recent cross-sectional correlational studies using self-report, on the relation between paternal and maternal parenting and child anxiety. Noguchi and Ollendick (2010) found that more family expressiveness as perceived by the father (e.g., "we say anything we want around the home") was in older youth with psychopathology (n = 178) associated with more social anxiety, whereas family expressiveness as perceived by the mother was associated with less youth social anxiety (the latter finding was in line with predictions that family expressiveness protects against social anxiety). Note however that most of the sample suffered from ADHD or oppositional defiant disorder, and social anxiety may actually be a protective factor against social impulsivity for these children.…”
Section: Top-down Studiessupporting
confidence: 78%
“…We identified four more recent cross-sectional correlational studies using self-report, on the relation between paternal and maternal parenting and child anxiety. Noguchi and Ollendick (2010) found that more family expressiveness as perceived by the father (e.g., "we say anything we want around the home") was in older youth with psychopathology (n = 178) associated with more social anxiety, whereas family expressiveness as perceived by the mother was associated with less youth social anxiety (the latter finding was in line with predictions that family expressiveness protects against social anxiety). Note however that most of the sample suffered from ADHD or oppositional defiant disorder, and social anxiety may actually be a protective factor against social impulsivity for these children.…”
Section: Top-down Studiessupporting
confidence: 78%
“…Previous studies have tended to focus on the impact of family factors on the development, risk and treatment of anxiety disorder (Rapee, 2012). In particular, family expressiveness is associated with social anxiety symptoms, with the family expressiveness reported by fathers positively related to social anxiety symptoms and the family expressiveness, which means the emotional expression from parents, reported by mothers negatively related to social anxiety symptoms (Noguchi & Ollendick, 2010). Hudson and Rapee (2005) noted that the family environment was latently influential during the development of some mental disorders, and other studies have identified that marriage conditions and family environment affect adolescents and emerging adults – particularly with regard to separation anxiety (Kins, Soenens, & Beyers, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Quality of relationship with the parent is, therefore, one potential moderator to be examined in future studies. There also appears to be differential relations among constructs based on child gender (Isley, O'Neil, Clatfelter, & Parke, 1999; Noguchi & Ollendick, 2010); unfortunately, we did not have a sufficient sample size to examine the moderating influence of child or parent gender.…”
Section: Discussionmentioning
confidence: 96%